O učinkovitosti in odgovornosti v sodstvu - Florjančič, Damijan (Podjetje in delo, 2020)
In the first part of the article, the author analyses different aspects of efficiency in the functioning of the judiciary. First the constitutional and legal bases for defining efficiency criteria are presented. Second, based on data from the Annual Report on the Efficiency and Effectiveness of Courts for 2019 of the Supreme Court of the Republic of Slovenia and data from the 2020 EU Justice Scoreboard, the author presents basic conclusions on the efficiency of the Slovenian judiciary. He estimates that the Slovenian judiciary is relatively efficient and, on average, comparable to most judicial systems in other EU countries. He emphasises the importance of new methodological approaches for monitoring the work and efficiency of the judiciary. In the second part of the article, the author addresses some issues related to the responsibility of the judiciary and in the judiciary. In doing so, he highlights different aspects of responsibility, namely institutional responsibility, at the level of the judiciary as a system, and individual responsibility, at the level of each individual judge. Their intertwining and interdependence is reflected in the fact that, at the institutional level, the judicial administration is established and responsible for ensuring appropriate working conditions for judges; on the other hand, the reflection of the work of each individual judge is reflected at the institutional level, which is ultimately perceived in the appropriate level of trust enjoyed by the judiciary in the public. In order to exercise institutional responsibility, appropriate external decision-making mechanisms have been established - the National Assembly and the Judicial Council; in order to assess the individual responsibility of judges, internal decision-making mechanisms have been established - personnel councils, which assess judicial service of individual judges, and a disciplinary court, which decides on disciplinary violations by judges.
Keywords: clearance rate; časovni standard; disciplinary proceedings; disciplinski postopek; disposition time; efficiency; evaluation of the judicial service; individual; individualna; institucionalna; institutional; judicial administration; judicial decision making; obvladovanje pripada; ocena sodniške službe; odgovornost; pričakovani čas rešitve; responsibility; sodna uprava; sodno odločanje; sojenje v razumnem roku; time standard; trial within a reasonable time; učinkovitost